The effect of hydrothermal treatment on metabolite composition of hass avocados stored in a controlled atmosphere - Chirinos, Rosana (2021)
Avocado cv. Hass consumption has expanded worldwide given its nutritional, sensory, and functional attributes. In this work, avocado fruit from two harvests was subjected to hydrothermal treatment (38 °C for 1 h) or left untreated (control) and then stored for 30 and 50 days in a controlled atmosphere (4 kPa O2 and 6 kPa CO2 at 7 °C) (HTCA and CA, respectively) with subsequent ripening at ~20 °C. The fruit was evaluated for primary and secondary metabolites at harvest, after storage, and after reaching edible ripeness. A decrease from harvest to edible ripeness in mannoheptulose and perseitol was observed while β-sitosterol, hydrophilic and lipophilic antioxidant activity (H-AOX, L-AOX), abscisic acid, and total phenolics (composed of p-coumaric and caffeic acids such as aglycones or their derivatives) increased. HTCA fruit at edible ripeness displayed higher contents of mannoheptulose, perseitol, β-sitosterol, L-AOX, caffeic acid, and p-coumaric acid derivatives, while CA fruit presented higher contents of α-tocopherol, H-AOX, and syringic acid glycoside for both harvests and storage times. The results indicate that a hydrothermal treatment prior to CA enables fruit of high nutritional value characterized by enhanced content of phenolic compounds at edible ripeness to reach distant markets.